Species Designations Belie Phenotypic and Genotypic Heterogeneity in Oral Streptococci - Velsko, Irina M. (mSystems, 2018)
Health-associated oral Streptococcus species are promising probiotic candidates to protect against dental caries. Ammonia production through the arginine deiminase system (ADS), which can increase the pH of oral biofilms, and direct antagonism of caries-associated bacterial species are desirable properties for oral probiotic strains. ADS and antagonistic activities can vary dramatically among individuals, but the genetic basis for these differences is unknown. We sequenced whole genomes of a diverse set of clinical oral Streptococcus isolates and examined the genetic basis of variability in ADS and antagonistic activities. A total of 113 isolates were included and represented 10 species: Streptococcus australis, A12-like, S. cristatus, S. gordonii, S. intermedius, S. mitis, S. oralis including S. oralis subsp. dentisani, S. parasanguinis, S. salivarius, and S. sanguinis. Mean ADS activity and antagonism on Streptococcus mutans UA159 were measured for each isolate, and each isolate was whole genome shotgun sequenced on an Illumina MiSeq. Phylogenies were built of genes known to be involved in ADS activity and antagonism. Several approaches to correlate the pan-genome with phenotypes were performed. Phylogenies of genes previously identified in ADS activity and antagonism grouped isolates by species, but not by phenotype. A genome-wide association study (GWAS) identified additional genes potentially involved in ADS activity or antagonism across all the isolates we sequenced as well as within several species. Phenotypic heterogeneity in oral streptococci is not necessarily reflected by genotype and is not species specific. Probiotic strains must be carefully selected based on characterization of each strain and not based on inclusion within a certain species. IMPORTANCE Representative type strains are commonly used to characterize bacterial species, yet species are phenotypically and genotypically heterogeneous. Conclusions about strain physiology and activity based on a single strain therefore may be inappropriate and misleading. When selecting strains for probiotic use, the assumption that all strains within a species share the same desired probiotic characteristics may result in selection of a strain that lacks the desired traits, and therefore makes a minimally effective or ineffective probiotic. Health-associated oral streptococci are promising candidates for anticaries probiotics, but strains need to be carefully selected based on observed phenotypes. We characterized the genotypes and anticaries phenotypes of strains from 10 species of oral streptococci and demonstrate poor correlation between genotype and phenotype across all species.